An Overview of the Classification, Production and Utilization of Biofuels for Internal Combustion Engine Applications - Awogbemi, Omojola; Von Kallon, Daramy Vandi; Onuh, Emmanuel Idoko (Energies, 2021)
Biofuel, a cost-effective, safe, and environmentally benign fuel produced from renewable sources, has been accepted as a sustainable replacement and a panacea for the damaging effects of the exploration for and consumption of fossil-based fuels. The current work examines the classification, generation, and utilization of biofuels, particularly in internal combustion engine (ICE) applications. Biofuels are classified according to their physical state, technology maturity, the generation of feedstock, and the generation of products. The methods of production and the advantages of the application of biogas, bioalcohol, and hydrogen in spark ignition engines, as well as biodiesel, Fischer– Tropsch fuel, and dimethyl ether in compression ignition engines, in terms of engine performance and emission are highlighted. The generation of biofuels from waste helps in waste minimization, proper waste disposal, and sanitation. The utilization of biofuels in ICEs improves engine performance and mitigates the emission of poisonous gases. There is a need for appropriate policy frameworks to promote commercial production and seamless deployment of these biofuels for transportation applications with a view to guaranteeing energy security.
Keywords: biodiesel; biofuel; emission; feedstock; utilization; transesterification; transportation; Nigeria; Power; University of Nigeria Nsukka; ACE_SPED; ACE: Sustainable Power and Energy Development